2013
DOI: 10.18172/cig.1218
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de la erosión en áreas acarcavadas en la Fm. Tudela (Bardenas Reales, Navarra)

Abstract: RESUMEN. En Bardenas RealesPalabras clave: badlands, gully, coladas de barro, bolas armadas de arcilla, polvo eólico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Since restoration has changed the landscape, we try to assess soil characteristics, composition of vegetation and cover and, therefore, their influence on erosion processes, runoff and suspended sediment concentration. This paper is important because the Saldaña Badlands are located in a sub‐humid continental Mediterranean climate, whereas most studies have been completed in wetter (Gallart et al ., ; Vallauri et al ., ; Nadal‐Romero et al ., ; Martínez‐Casasnovas et al ., ; Clarke and Rendell, ); warmer (Boix‐Fayos et al ., ); and/or drier (Finlayson et al ., ; Cerdá, ; Cantón et al ., ; Castillo et al ., ; Faulkner et al ., ; Desir and Marín, ; Laudicina et al ., ) environments.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since restoration has changed the landscape, we try to assess soil characteristics, composition of vegetation and cover and, therefore, their influence on erosion processes, runoff and suspended sediment concentration. This paper is important because the Saldaña Badlands are located in a sub‐humid continental Mediterranean climate, whereas most studies have been completed in wetter (Gallart et al ., ; Vallauri et al ., ; Nadal‐Romero et al ., ; Martínez‐Casasnovas et al ., ; Clarke and Rendell, ); warmer (Boix‐Fayos et al ., ); and/or drier (Finlayson et al ., ; Cerdá, ; Cantón et al ., ; Castillo et al ., ; Faulkner et al ., ; Desir and Marín, ; Laudicina et al ., ) environments.…”
Section: Introductionmentioning
confidence: 99%
“…They have also observed that the lowest zone of the badlands varied from 0.36 mm yr ‐1 deposition to 0.06 mm yr ‐1 surface lowering. In Spain, Desir and Marín () measured high erosion rates in non‐vegetated badlands of the Bárdenas Reales, ranging from 32 to 77 Mg ha ‐1 yr ‐1 . In contrast, Cantón et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Para predecir la degradación de los suelos por erosión hídrica se han utilizado ampliamente diferentes métodos que permiten identificar pérdidas actuales y 3 potenciales no tolerables, sobre la base de las cuales se seleccionan las mejores prácticas de control de la erosión (Desir y Marín, 2009;Oñate 2004). Los aspectos anteriores justifican el desarrollo de una investigación donde el principal objetivo es estimar la agresividad climática en el sector hidrogeológico CA-II-I del municipio de Venezuela en la provincia Ciego de Ávila, Cuba a través del Índice Modificado de Fournier y el ajuste a la función de distribución de Gumbel asociados a los períodos de retornos que contribuya a la evaluación del comportamiento futuro de este fenómeno y permita trazar estrategias para la conservación del suelo en las áreas agrícolas donde se desarrolla la investigación.…”
Section: Introductionunclassified